STUDI INTERVENSI BAGI GURU DI INDONESIA UNTUK MENANGANI ANAK BERKELUARBIASAAN GANDA (TWE) DI KELAS - Maliha, Siti (Jurnal Bimbingan dan Konseling Borneo, 2022)
The talents of TWE (twice-exceptional) children often mask their weaknesses or vice versa. The aim of this intervention study was to increase teachers’ knowledge and familiarities with twice exceptional children as well as to introduce strategies that would enhance the experiences of these children in the classroom. This program for teaching twice-exceptional children was based on the Response to Intervention (RTI) approach (Fuchs Fuchs, 2005) to delivering different types of interventions to students based on their needs. In this research, the intervention consisted of four weeks training including tutorials, focus group discussions (FGDs), role-plays, and evaluations. The research was conducted with 61 primary school teachers from ten primary schools in different regions/districts in Jakarta, Indonesia. There was a pre-intervention test before the implementation of the intervention and a post-intervention test to evaluate the intervention. A mixed-model analysis of variance (ANOVA) has been used to analyse the data. The between-subject factor was Condition (Intervention vs. Control) while the within-subject factor was Time (pre/baseline vs. post/time 2). The intervention sessions resulted in teachers having now learned and being more aware of the characteristics of TWE children with the hope that they will implement the RTI framework in their schoolsKeywords : TWE (twice-exceptional) children, teachers, intervention, RTI (Response to Intervention) framework, familiarity, experiences.